Pengaruh Penggunaan Variasi Berat Mat Serbuk Bunga Kenanga (Cananga odorata) Sebagai Isi Ulang Anti Nyamuk Elektrik Terhadap Jumlah Kematian Nyamuk Aedes sp. - Kabul Budi Dwicahyo; Sarjito Eko Windarso; Indah Werdiningsih (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
Controlling Aedes sp. mosquitoes using anti-mosquitoes containing synthetic insecticide, con-tinuously, is harmful for humans’ health, causing mosquitoes resistance and may lead to envi-ronmental pollution. One of the safe and eco-friendly controlling method that can be used as an alternative solution is the using of ylang-ylang flower (Cananga odorata) powder which contains phyto-insecticide as anti-mosquitoes electrical device refill. The aim of this research was to know the effect of using three mat weight variations made from the flower powder on the morta-lity of adult Aedes sp., by conducting an experiment with post test only with control group de-sign. The total of mosquito sample used were 480 and were taken from those hatched from the eggs obtained from the BBTKL PPM of Yogyakarta. They were prepared for six repetitions of the treatment. The results showed that mats with Cananga odorata weight of 2,4 gram, 3,7 gram and 5,0 gram, was able to killed 63,33 %, 74,17 % and 88,33 % Aedes sp mosquito, consecutively. The result of subsequent one way anova test at 95 % degree of confidence, gained p values less than 0,001, which can be interpreted that the mat weight variation sig-nificantly affected the difference among the Aedes sp. mosquitoes’ mortality, and the most ef-fective weight of ylang-ylang powder was 5,0 gram.